Communicating with Deaf Patients in the Clinical Environment through Deaf-Hearing Teams: Lessons Learned from a Virtual Patient Panel [version 2; peer review: 2 approved] - Dimitrios Papanagnou; Natalie P. Snyder; Rosemary Frasso; Benedicta O. Olonilua; Julia Croce (MedEdPublish)
Background Communication and cultural differences predispose Deaf patients to suboptimal healthcare. Despite this disparity, health professionals have historically received little to no training in caring for Deaf patients. Patient panels are an effective tool in medical education to model communication strategies. Objective In this paper, we describe the design, implementation, and results of a virtual patient panel focused on communicating with Deaf patients in clinical contexts. We offer practical suggestions for incorporating similar educational interventions in health professions education to prepare trainees to effectively navigate these conversations with their patients. Methods The panel consisted of a one-hour question and answer discussion facilitated by the authors with Deaf patients and Certified Deaf Interpreters (CDI). The panel was presented to 271 second-year medical students at our institution in November of 2023. Following this discussion, students were encouraged to share one or two key takeaways from the session through a survey link. These results were analyzed using pile-sorting qualitative analysis to identify main themes. Results There were 73 respondents, with a response rate of 27%. After the panel, the most popular takeaway points from student reflections included communication (n=56, 77%) and access to care (n=47, 64%), followed by autonomy (n=17, 23%), the doctor-patient relationship (n=15, 21%), and culture (n=11, 15%). Based on this initiative, we identified and offer twelve tips for developing similar exercises. These tips are thematically presented under three groupings: Virtual Panel Considerations, Curricular Considerations, and Special Considerations with Deaf Panelists. Conclusion This patient panel was the first of its kind in our medical school curriculum. Important considerations in panel design and implementation should focus on delivery time constraints with live-interpreting and further exploring the role of trust and communication in the physician-patient relationship.